2000
DOI: 10.1046/j.1365-2958.2000.01905.x
|View full text |Cite
|
Sign up to set email alerts
|

Variable human minisatellite‐like regions in the Mycobacterium tuberculosis genome

Abstract: Mycobacterial interspersed repetitive units (MIRUs) are 40–100 bp DNA elements often found as tandem repeats and dispersed in intergenic regions of the Mycobacterium tuberculosis complex genomes. The M. tuberculosis H37Rv chromosome contains 41 MIRU loci. After polymerase chain reaction (PCR) and sequence analyses of these loci in 31 M. tuberculosis complex strains, 12 of them were found to display variations in tandem repeat copy numbers and, in most cases, sequence variations between repeat units as well. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
451
2
19

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 483 publications
(484 citation statements)
references
References 48 publications
(79 reference statements)
12
451
2
19
Order By: Relevance
“…This deficiency is partially solved with spoligotyping as a secondary method (Cowan et al 2005). Our results also corroborate a previous proposition that it is ultimately MIRU typing that will resolve the problems stemming from low-IS6110-copy strains (Supply et al 2000); indeed, IS6110-RFLP typing in other parts of India has revealed the presence of a 2 3 3 3 2 1 82 00134 EAI3-IND 2 3 4 3 *6 3 3 3 3 2 4 83 00374 EAI3-IND 2 5 3 3 *6 2 3 3 3 2 4 84 00378 EAI3-IND 2 5 3 2 *6 3 2 3 5 2 3 85 00652 EAI3-IND 2 3 3 2 *6 2 2 3 5 2 2 86 00660 EAI3-IND 2 3 3 2 *6 2 2 3 4 3 3 87 00938 EAI3-IND 1 5 5 4 *6 2 3 3 5 3 3 88 03390 EAI3-IND 2 3 6 4 *6 3 2 4 8 3 3 89 05431 EAI3-IND 2 3 3 3 *7 2 4 3 3 2 5 90 …”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…This deficiency is partially solved with spoligotyping as a secondary method (Cowan et al 2005). Our results also corroborate a previous proposition that it is ultimately MIRU typing that will resolve the problems stemming from low-IS6110-copy strains (Supply et al 2000); indeed, IS6110-RFLP typing in other parts of India has revealed the presence of a 2 3 3 3 2 1 82 00134 EAI3-IND 2 3 4 3 *6 3 3 3 3 2 4 83 00374 EAI3-IND 2 5 3 3 *6 2 3 3 3 2 4 84 00378 EAI3-IND 2 5 3 2 *6 3 2 3 5 2 3 85 00652 EAI3-IND 2 3 3 2 *6 2 2 3 5 2 2 86 00660 EAI3-IND 2 3 3 2 *6 2 2 3 4 3 3 87 00938 EAI3-IND 1 5 5 4 *6 2 3 3 5 3 3 88 03390 EAI3-IND 2 3 6 4 *6 3 2 4 8 3 3 89 05431 EAI3-IND 2 3 3 3 *7 2 4 3 3 2 5 90 …”
Section: Discussionsupporting
confidence: 86%
“…Though unusual for high-banded strains, similar findings have been reported by other investigators who reported isolates within IS6110-RFLP clusters that differed by two-seven loci in a 24 loci MIRU-VNTR assay (Shamputa et al 2010). We used primers for 11 loci from the original set of 12 loci used in earlier studies (Supply et al 2000). Valcheva et al (2008) compared the use of 12, 15 and 24 loci to genotype 73 strains of M. tuberculosis.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations